Ultimate Spider-Man. [Vol. 06] : Venom. - Bendis, Brian Michael (Spider-Man, 2003)
Spider-Man's meeting with childhood friend Eddie Brock and the revelation of a secret from their fathers' past, forces Spidey into a confrontation with his evil twin, Venom.